Uterine artery embolisation for uterine myoma — a case series - D. S. Rossolko; T. I. Prohorovich; Sh. S. Dzhanibekova; V. V. Vasilev; M. N. Pavelyeva (Лечащий Врач)
Background. To date, there is quite a lot of international experience with uterine artery embolisation. This method is an alternative to classical myomectomy and differs from it by less invasiveness and surgical trauma, and faster rehabilitation. Endovascular intervention, despite a fairly good evidence base for its effectiveness, still cannot be used routinely for reasons of fertility preservation, oncovigilance, and effectiveness. There is a need to study the postoperative results of uterine artery embolization in patients with uterine myoma from two approaches (transfemoral and transradial), compare them with each other and with the results of hysteroresectoscopy.Results. This retrospective single-center study evaluates the results of treatment of a single symptomatic submucous myoma up to 7 centimeters in size. Such treatment methods as classical hysteroresectoscopy and uterine artery embolization from transradial and transsphenoidal approaches are compared. Clinical observations for 24 months were collected, according to the results it was noted that endovascular interventions are safer (lower frequency of early postoperative complications of pulmonary embolism and panmetritis), at the same time, the effectiveness of the intervention is lower if we evaluate such parameters as recurrence of abnormal uterine bleeding, time to restoration of the normal menstrual cycle.Conclusion. Endovascular embolization of uterine arteries in comparison with hysteroresectoscopy is a safer intervention, which can be concluded when evaluating early postoperative results. At the same time, in terms of effectiveness in the treatment of uterine fibroids, endovascular intervention is inferior in terms of freedom from recurrence of abnormal uterine bleeding, time of normalization of the menstrual cycle. The choice of endovascular access for endovascular embolization of uterine arteries does not affect the gynecological outcome of treatment, at the same time, with transradial access, a lower frequency of hematoma formation is noted.